PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN DAN LOYALITAS PELANGGAN HARDY’S NEGARA - Satya Graha, I Made; Wardana, Made (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.05.NO.02.TAHUN 2016, 2016)
The ritel business that exist in Negara city has been experiences fast development. The development cause by the ritail customer more like to buy the different good in one place. Many retail place offering many easy in shopping start from service given, discount, payment selection, and others facility to create satisfaction for the customer. The method used in this research is the study of causality. The sampling technique used is purposive sampling with a sample size of 130 respondents. The research instrument using a questionnaire with a scale semantic difrensial. Data analysis technique using SEM (structural equation model).The results showed the quality of services provided by the State Hardy's positive and significant impact on customer satisfaction. This means that the better quality of service to customers, it can improve customer satisfaction Hardy's Negara. This means that the better the quality of services provided to customers, the higher the customer loyalty behavior, and conversely the bad quality of services provided, the lower the level of customer loyalty and customer satisfaction and significant positive effect on customer loyalty Hardy's Negara. This means that the better the quality of services provided to customers, the higher the level of their desire to apply loyal, otherwise the worse the perceived satisfaction then the lower the desire of consumers to apply loyal. Hardy's suggestion for the State to be more focused on creating customer satisfaction as give discounts on every purchase with a specific nominal and further emphasize customer satisfaction programs are better able to make a valid loyal customers.
Keywords: service quality, satisfaction, loyalty, customer